Influence of starch deficiency on photosynthetic and post-photosynthetic carbon isotope fractionations. (9th February 2019) - Lehmann, Marco M; Ghiasi, Shiva; George, Gavin M; Cormier, Marc-André; Gessler, Arthur; Saurer, Matthias; Werner, Roland A
Abstract : Carbon isotope composition of starch-deficient mutants is primarily explained by photosynthetic 13 C fractionations, and thus plant physiological responses to changes in carbon storage, rather than by post-photosynthetic 13 C fractionations.  Abstract: Carbon isotope ( 13 C) fractionations occurring during and after photosynthetic CO2 fixation shape the carbon isotope composition (δ 13 C) of plant material and respired CO2 . However, responses of 13 C fractionations to diel variation in starch metabolism in the leaf are not fully understood. Here we measured δ 13 C of organic matter (δ 13 COM ), concentrations and δ 13 C of potential respiratory substrates, δ 13 C of dark-respired CO2 (δ 13 CR ), and gas exchange in leaves of starch-deficient plastidial phosphoglucomutase ( pgm ) mutants and wild-type plants of four species ( Arabidopsis thaliana, Mesembryanthemum crystallinum, Nicotiana sylvestris, and Pisum sativum ). The strongest δ 13 C response to the pgm -induced starch deficiency was observed in N. sylvestris, with more negative δ 13 COM, δ 13 CR, and δ 13 C values for assimilates (i.e. sugars and starch) and organic acids (i.e. malate and citrate) in pgm mutants than in wild-type plants during a diel cycle. The genotype differences in δ 13 C values could be largely explained by differences in leaf gas exchange. In contrast, the PGM-knockout effect on post-photosynthetic 13 C fractionations via the plastidic fructose-1, 6-bisphosphate aldolase reaction or during respiration was small. Taken together, our results show that the δ 13 C variations in starch-deficient mutants are primarily explained by photosynthetic 13 C fractionations and that the combination of knockout mutants and isotope analyses allows additional insights into plant metabolism.